Melatonin enhances ovarian response in infertile women with polycystic ovary syndrome (Bangladesh Journal of Medical Science, 2023)
Background: Polycystic ovary syndrome (PCOS) is a common endocrine disorder in women of reproductive age.Anovulation, decreased Oocyte quality and low endometrial receptivity are the cause of infertility in women withPCOS. Anovulation is the consequence of hyperandrogenism, insulin resistance. Furthermore, the reactive oxygenspecies (ROS) induce oxidative stress which may be responsible for poor Oocyte quality. Melatonin is a documentedpowerful free radical scavenger and broad-spectrum antioxidant. Current evidence suggests that melatonin involvesin ovarian physiology including follicular development, ovulation, and oocyte maturation. Present study was triedto evaluate the effects of melatonin on biochemical parameters as well as outcomes of ovulation induction byletrozole in infertile women with polycystic ovary syndrome.Method: This study including 74 women of Polycystic Ovary Syndrome (PCOS) with infertility. Intervention group received melatonin 3 mg at bed time for 8 weeks as pretreatment. Serum luteinizing hormone (LH), testosterone, anti mullerian hormone (AMH), fasting insulin, oral glucose tolerance test (OGTT) were measured at baseline and after 8 weeks. Both intervention and control group were received ovulation induction for 3 cycles by Letrozole (5 mg from cycle days 2 to 6). Intervention group continued melatonin until mature follicle achieved. The primary outcomes were biochemical changes by serum luteinizing hormone (LH), testosterone, anti mullerian hormone (AMH), fasting insulin, oral glucose tolerance test (OGTT) and ovarian responses by number of mature follicles, endometrial thickness and ovulation rate. Secondary outcome was pregnancy rate.Result: Melatonin treatment for 8 weeks significantly decreased testosterone (P